2012
DOI: 10.1007/s00426-012-0413-4
|View full text |Cite
|
Sign up to set email alerts
|

The impact of task rules on distracter processing: automatic categorization of irrelevant stimuli

Abstract: The goal of the study was to investigate whether task rules are automatically applied to irrelevant distracters. In three experiments, subjects categorized target words which were superimposed on distracter pictures. The categorization rule was arbitrary and the distracters were not relevant at any point during the experiment. We found congruency effects for distracters that belonged to the task-relevant categories, but were never presented as target words. Responses were faster when target and distracter belo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
38
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(43 citation statements)
references
References 31 publications
5
38
0
Order By: Relevance
“…Therefore, when participants searched for X or N in a centrally presented visual array, those letters were taskrelevant if they occurred anywhere in the visual scene, and as Tellinghuisen and Nowak (2003) demonstrated, even if they occurred in the auditory modality. Reisenauer and Dreisbach (2013) directly tested how task performance rules and subsequent response activations influenced the processing of to-be-ignored picture distractors in a two-alternative forced choice visual-word categorization task. Participants responded to trials in which a single word was superimposed over a picture (e.g., the word flag superimposed on a picture of a spinning top), in which words were the targets, while the pictures were to be ignored.…”
Section: Attention and Processing Task-related Stimulimentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, when participants searched for X or N in a centrally presented visual array, those letters were taskrelevant if they occurred anywhere in the visual scene, and as Tellinghuisen and Nowak (2003) demonstrated, even if they occurred in the auditory modality. Reisenauer and Dreisbach (2013) directly tested how task performance rules and subsequent response activations influenced the processing of to-be-ignored picture distractors in a two-alternative forced choice visual-word categorization task. Participants responded to trials in which a single word was superimposed over a picture (e.g., the word flag superimposed on a picture of a spinning top), in which words were the targets, while the pictures were to be ignored.…”
Section: Attention and Processing Task-related Stimulimentioning
confidence: 99%
“…In addition, such congruency effects were found even for picture stimuli that were not part of the target set (i.e., pictures of objects that never appeared as target words). Reisenauer and Dreisbach (2013) concluded that in the task rule condition, response interference occurred because the implementation of a relevant task rule increased processing of all task-related stimulus features, even if the features occurred in a to-be-ignored picture. The categorization rules set by the task instructions were the critical variable determining which word-picture combinations influenced the speed of processing.…”
Section: Attention and Processing Task-related Stimulimentioning
confidence: 99%
See 3 more Smart Citations